Prolonged impairment of immunological memory after anti-CD20 treatment in pediatric idiopathic nephrotic syndrome: an extended follow-up - Colucci, Manuela; Riganati, Martina; Zotta, Federica; Gargiulo, Antonio; Massella, Laura; Ruggiero, Barbara; Cotugno, Nicola; Ricci, Giulia; Palma, Paolo; Emma, Francesco; Vivarelli, Marina (Frontiers in Immunology, 2025)
IntroductionAnti-CD20 therapy is an effective steroid-sparing option for pediatric idiopathic nephrotic syndrome (INS), but long-term data on immune reconstitution are limited.MethodsThirteen pediatric INS patients (7 males) were longitudinally evaluated at baseline, first long-term follow-up (mean 5.4 years), and extended follow-up (mean 6.6 years after the first follow-up, >3 years from the last anti-CD20 infusion). Clinical outcomes, B-cell subsets, serum immunoglobulin levels, vaccine competence, and infection rates were analyzed.ResultsAt the first follow-up, most patients had received one (n=6) or two (n=6) anti-CD20 courses; at the extended follow-up, five had undergone additional treatments. Four patients remained relapse-free during follow-up, whereas eight of nine who had previously relapsed continued to experience disease recurrence despite further anti-CD20 therapy. Oral immunosuppressant tapering improved: three patients were off therapy at first follow-up and six at the latest. Total, transitional and mature-naïve B cells reconstituted to normal ranges according to age over time. In contrast, total, IgM, and switched memory B cells remained significantly reduced (p<0.01). Patients in sustained remission exhibited lower switched memory B-cell counts than relapsing patients (p<0.05). Serum IgG levels increased at the extended follow-up, although six patients remained below normal. Four developed severe de novo hypogammaglobulinemia requiring long-term immunoglobulin replacement and showing increased infection susceptibility. Vaccine-specific IgG titers against tetanus and HBV remained below the limit of seroprotection despite re-immunization in most patients.ConclusionsAnti-CD20 therapy offers durable disease control and allows immunosuppressant reduction in pediatric INS, but persistent memory B-cell and humoral impairment warrant long-term immunologic monitoring.